Islamic banking risk management: Trends and insights from a bibliometric and SLR approach - Nuzulia, Nuzulia; Kasanah, Roisatun (Universitas Islam Negeri Raden Mas Said Surakarta, 2024)
Along with the growth of Islamic banking, risk management is an essential element that must be managed properly because it is one of the potential financial institutions. This study aims to see trends and analyze the development of research on risk management in Islamic banking by reviewing the literature through bibliometric methods and systematic literature review (S.L.R.). The findings of this study are the number of articles related to Islamic banking risks that have been carried out from 2002 to 2022, with a total of 372 articles. Based on the analysis, it can be seen that the number of articles published increased and peaked in 2018. Operational risk and risk management practices keywords are the least numerous. This result showed that Islamic banking has different characteristics than conventional banking, including financial risk and non-financial risk, thus requiring a different regulatory approach in the mitigation and stabilization process. Furthermore, this study highlights gaps in the literature, such as the limited focus on operational risks, and offers a comprehensive framework for understanding risk management practices in Islamic banking. These findings contribute to theoretical advancements by emphasizing the need for regulatory frameworks tailored to the unique characteristics of Islamic banking, filling a critical gap in existing research.